Phosphorus price spikes: A wake-up call for phosphorus resilience - Brownlie, Will J.; Sutton, Mark A.; Cordell, Dana; Reay, Dave S.; Heal, Kate V.; Withers, Paul J. A.; Vanderbeck, Isabelle; Spears, Bryan M. (Frontiers in Sustainable Food Systems, 2023)
Food systems depend on reliable supplies of phosphorus to fertilize soils. Since 2020, a pandemic, geopolitical disputes, trade wars and escalating fuel prices have driven a >400% increase in phosphorus commodity prices, contributing to the current food crisis. The Russia-Ukraine conflict has disrupted phosphate trade further. Concurrently, phosphorus losses to freshwaters, through insufficient municipal wastewater treatment and inappropriate fertilizer use and land management practices, are a significant threat to water quality globally. Despite precariously balanced food and water security risks, nations are largely unaware of their “phosphorus vulnerability” and phosphorus is markedly absent in national and global policies addressing food and water security. Phosphorus vulnerability can be described as the degree to which people/systems are susceptible to harm due to the physical, geopolitical and socio-economic dimensions of global phosphorus scarcity and pollution. Here, we bring the current price spike into focus, highlighting the drivers, policy responses and their consequences. We highlight the need for an integrated assessment of phosphorus vulnerability that considers environmental, socio-economic and climate change risks across scales. We illustrate how reducing phosphorus waste, increasing phosphorus recycling, and wider system transformation can reduce national reliance on imported phosphorus, whilst enhancing food and water security. The current crisis in fertilizer prices represents a wake-up call for the international community to embrace the global phosphorus challenge.